Evaluation of field work practice program of electrical vocational high school in the Bandar Lampung City - Dwi Feriyanto; Djoko Laras Budiyo Taruno (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
The competence acquired participants of field work practice (FWP) are not all in accordance with the competency of skills in Electrical Vocational High School. This research aims to know the discrepancy of organizing FWP Electrical Vocational High School, in terms of: (1) planning of program, (2) implementation of program, (3) assessment of programs, (4) financing of program. Data collection using the closed questionnaire, interviews and documentation. The data were analyzed using mixed method with sequential explanatory design. Research results are known: (1) the success of the program planning aspects of FWP with a mean of 78.74% and discrepancy of 21.26%, (2) the success of program implementation aspects of FWP with average 84.37% and discrepancy 15.63%,  (3) the success of the program assessment aspects of FWP with a mean of 79.64% and 20.36% amounting to discrepancy, (4) the success of financing program aspects of FWP with a mean of 55.83% and discrepancy of 44.17%.